High Resolution STEM-EELS Study of Silver Nanoparticles Exposed to Light and Humic Substances - Richard Palmer (Environmental Science & Technology, 2016)
Nanoparticles (NPs) are defined as particles with at least one dimension between 1 and 100 nm or with properties that differ from their bulk material, which possess unique properties. The extensive use of NPs means that discharge to the environment is likely increasing, but fate, behavior, and effects under environmentally relevant conditions are insufficiently studied. This paper focuses on the transformations of silver nanoparticles (AgNPs) under simulated but realistic environmental conditions. High resolution aberration-corrected scanning transmission electron microscopy (HAADF STEM) coupled with electron energy loss spectroscopy (EELS) and UV–vis were used within a multimethod approach to study morphology, surface chemistry transformations, and corona formation. Although loss, most likely by dissolution, was observed, there was no direct evidence of oxidation from the STEM-EELS. However, in the presence of fulvic acid (FA), a 1.3 nm oxygen-containing corona was observed around the AgNPs in water; modeled data based on the HAADF signal at near atomic resolution suggest this was an FA corona was formed and was not silver oxide, which was coherent (i.e., fully coated in FA), where observed. The corona further colloidally stabilized the NPs for periods of weeks to months, dependent on the solution conditions.